Sistem Informasi Estimasi Potensi Tenaga Air Perncanaan Pembangkit Listrik Di Kiayo Kalimantan Barat - Prayogi, Sukma; Tanuwijaya, Haryanto (Jurnal JSIKA, 2012)
Planning is the beginning of an activity. One of the activities of planning is to estimate the potential of hydropower in electricity generation planning. Because there is still any facility or information system tools that can assist in the calculation, calculations performed with the help of Excel tools. Planners must design and create a formula, the formula used manual input, print all the data and combine the print is to be able to meet the desired report. Gumbel method used in calculating the maximum rainfall perperiode, while for Melchior, Weduwen, and Hasper method used in the calculation of the maximum flood discharge perperiode. Alternative power generated is calculated based on water availability. The calculation is done to assist in the analysis of power plant construction location. Keywords :Gumbel, Melchior, Weduwen, Hasper, Power Plant